Body asymmetry and sports specialization: An exploratory anthropometric comparison of adolescent canoeists and kayakers - Herrera-Amante, C. A.; Carvajal-Veitía, W.; Yáñez-Sepúlveda, R.; Alacid, F.; Gavala-González, J.; López-Gil, J. F.; Olivares-Arancibia, J.; Ramos-García, C. O. (Journal of Functional Morphology and Kinesiology, 2025)
Background/Objectives: The evaluation of body asymmetry between the right and left sides of the body is crucial in the context of sports because of its potential impact on performance and injury prevention. This study analyzed the anthropometric differences between the right and left sides of the body in adolescent (13.0 [2.0] years) male canoeists and kayakers from Spain. This study aimed to explore the asymmetries associated with these disciplines.